2001
DOI: 10.1093/mutage/16.5.377
|View full text |Cite
|
Sign up to set email alerts
|

Lack of change in the levels of liver and kidney cytochrome P-450 isozymes in p53(+/-) knockout mice treated with N-butyl-N-(4-hydroxybutyl)nitrosamine

Abstract: We have previously shown that p53(+/-) knockout mice are highly sensitive to urinary bladder carcinogenesis induced by N-butyl-N-(4-hydroxybutyl)nitrosamine (BBN) in spite of a lack of effects of p53 heterozygosity on N-butyl-N-(3-carboxypropyl)nitrosamine (BCPN) excretion in urine. To determine the influence of p53 deficiency on in vitro formation of BCPN, mutagenicity of BBN and BCPN and levels of several cytochrome P450 (CYP) isozymes, groups of five p53(+/-) knockout and wild-type mice (littermates), as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
3
6
0
Order By: Relevance
“…In the present study, although rats were given 0.05% BBN in drinking water for 8 weeks, the treatment produced no obvious effects on the levels of any CYP species, including CYP2E1 and 2B1/2, as determined in liver or kidney. This is in agreement with the findings for rat CYP1A1/2 and 2B1/2, ( 36 ) and mouse CYP1A1/2, 2B, 2E1, and 3A ( 22 ) in these organs. In order to find which CYP species in liver or kidney was involved in the strain difference, HCA activated by CYP1A1/2 and N ‐nitrosamines activated by CYP2B1/2 and/or 2E1 were used in mutagenicity tests.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, although rats were given 0.05% BBN in drinking water for 8 weeks, the treatment produced no obvious effects on the levels of any CYP species, including CYP2E1 and 2B1/2, as determined in liver or kidney. This is in agreement with the findings for rat CYP1A1/2 and 2B1/2, ( 36 ) and mouse CYP1A1/2, 2B, 2E1, and 3A ( 22 ) in these organs. In order to find which CYP species in liver or kidney was involved in the strain difference, HCA activated by CYP1A1/2 and N ‐nitrosamines activated by CYP2B1/2 and/or 2E1 were used in mutagenicity tests.…”
Section: Discussionsupporting
confidence: 93%
“…The mutagenicity of these carcinogens was checked in the presence of liver or kidney S9, according to the methods described by Mori et al . ( 22 ) The amount of tissue S9 from rats was 150 µL/plate, except for liver S9 for HCA (10 µL/plate). The S9 mix contained the cofactors 4 mM NADPH, 4 mM NADH, 0.5 U G6PDH, 5 mM G6P, and 5 mM ATP for HCA and 4 mM NADP + and 5 mM G6P for DMN, DEN and BBN.…”
Section: Methodsmentioning
confidence: 99%
“…The CYP1A1 gene, which has been found to be induced by mainstream cigarette smoke in the nasal epithelium and lung of Sprague-Dawley rats (20) and by environmental cigarette smoke in skin and lungs of SKH-1 hairless mice (21), was not included in the cDNA array used. The poor effect of p53 mutation on the metabolic activation or detoxification of environmental cigarette smoke components is in agreement with the finding that the metabolic activation of nitrosamines was not altered in p53ϩ/Ϫ knockout mice (44). Moreover, the expression of CYP1A2 and GST-␣ genes was similar in the liver of wt and p53ϩ/Ϫ mice (45).…”
Section: Discussionsupporting
confidence: 89%
“…3). Primary Ab 3, a rabbit polyclonal developed against rat CYP3A2, has been suggested to recognize mouse CYP3A11 and 3A13 (Mori et al, 2001). Focusing on the upper band a recognized by this antibody, thought to represent CYP3A11, we found that MC decreased CYP3A11 immunoreactivity at days 2, 3 and 4 with the maximum suppression observed at day 2 (40% of vehicle control) (Fig.…”
Section: Resultsmentioning
confidence: 73%